Implication of the box C/D snoRNP assembly factor Rsa1p in U3 snoRNP assembly. Issue 12 (13th May 2017) - Rothé, Benjamin; Manival, Xavier; Rolland, Nicolas; Charron, Christophe; Senty-Ségault, Véronique; Branlant, Christiane; Charpentier, Bruno
Abstract: The U3 box C/D snoRNA is one key element of 90S pre-ribosome. It contains a 5΄ domain pairing with pre-rRNA and the U3B/C and U3C΄/D motifs for U3 packaging into a unique small nucleolar ribonucleoprotein particle (snoRNP). The RNA-binding protein Snu13/SNU13 nucleates on U3B/C the assembly of box C/D proteins Nop1p/FBL and Nop56p/NOP56, and the U3-specific protein Rrp9p/U3-55K. Snu13p/SNU13 has a much lower affinity for U3C΄/D but nevertheless forms on this motif an RNP with box C/D proteins Nop1p/FBL and Nop58p/NOP58. In this study, we characterized the influence of the RNP assembly protein Rsa1 in the early steps of U3 snoRNP biogenesis in yeast and we propose a refined model of U3 snoRNP biogenesis. While recombinant Snu13p enhances the binding of Rrp9p to U3B/C, we observed that Rsa1p has no effect on this activity but forms with Snu13p and Rrp9p a U3B/C pre-RNP. In contrast, we found that Rsa1p enhances Snu13p binding on U3C΄/D . RNA footprinting experiments indicate that this positive effect most likely occurs by direct contacts of Rsa1p with the U3 snoRNA 5΄ domain. In light of the recent U3 snoRNP cryo-EM structures, our data suggest that Rsa1p has a dual role by also preventing formation of a pre-mature functional U3 RNP.